Asymmetry of shocks and convergence in selected Asean countries: a dynamic analysis - Cortinhas, Carlos (2006)
This paper aims to investigate whether structural shocks among ASEAN countries are becoming more symmetrical over time, thus indicating whether this region is becoming betterprepared to introduce a common monetary policy. For that purpose a dynamic space-state model that complements the conventional Structural VAR models used in the existing literature was estimated by using the Kalman filter so that the evolution of the degree of shock symmetry and, therefore, the evolution in the degree of convergence could be identified over time, distinguishing between a country’s convergence with a regional partner and a more general trend of convergence with the rest of the world. The results showed that in the majority of cases there has been an increase in the degree of convergence of demand shocks in recent years. More importantly, it also showed an increase in divergence in supply shocks for most cases since the beginning of the 90’s even when taking into account the Asian Financial Crisis. This is especially true for the periphery countries suggesting that the Philippines and Thailand are not only not converging but actually diverging from the core group. These results have important implications for the prospects of the creation of a common monetary policy in the region.